SAT0335 Differential Modulation of The Chromogranin-A System in Takayasu Arteritis and Systemic Lupus Erythematosus. (15th July 2016) - Tombetti, E.; Colombo, B.; Di Chio, M.C.; Sartorelli, S.; Tombolini, E.; Ramirez, G.; Papa, M.; Baldissera, E.; Sabbadini, M.G.; De Cobelli, F.; Corti, A.; Manfredi, A.A.
Abstract : Background: Chromogranin-A (CgA) is a multi-source protein proteolitically processed into a family of peptides with various paracrine and endocrine functions. CgA-derived peptides influence vascular biology and neoangiogenesis: CgA1–439 (CgA439) and vasostatin-1 (VS1, CgA1–76) have anti-angiogenic properties, while fragments lacking the C-terminal domain (CgA-FRs) are pro-angiogenic. The mechanisms regulating vascular events and systemic inflammation in Takayasu Arteritis (TA) and Systemic Lupus Erythematosus (SLE) are poorly characterized. Objectives: To evaluate how the CgA system is modulated in TA and SLE Methods: 42 consecutive patients (pts) with TA were enrolled and matched with 20 age- and sex- matched SLE pts and 20 healthy subjects (HCs). Exclusion criteria were moderate/severe heart failure or contraindication to MR angiography (MRA). TA pts were longitudinally studied with 2 MRAs (12 months apart). Disease activity was assessed with NIH criteria and SLEDAI in the TA and SLE group, respectively. Arterial progression was defined as the appearance of new lesions or worsening of pre-existing lesions at MRA. CgA peptides and total CgA (CgAtot) were quantified with validated ELISAs. CgA processing was studied by ratios of CgA peptides to CgAtot. The antiangiogenic CgA potential was quantified in TA by summing the ranks of CgA439 and VS1. Results: Median age of TA patients (39W, 3M) was 46 (IQR 34–54) years. Median disease duration was 10 (IQR 7–14) years for TA, and 13 (7–21) years for SLE. Twelve TA and 8 SLE pts had active disease. Thirty TA and 10 SLE pts received proton pump inhibitors (PPI), which are known to increase CgA levels. Nine TA pts (8 treated with PPIs) underwent arterial progression. Serum CgA-FR were significantly higher in TA pts than in SLE pts (p<0.001) and HCs (p<0.001); VS1 was higher in SLE and TA than HCs (p<0.001 and p=0.020, Fig 1 A). CgA processing was similar in TA and HCs; a distinctive processing was evident in SLE, with higher VS1/CgAtot (p<0.001 Vs Ta and HCs) and lower CgA-FR/CgAtot (p=0.001 Vs TA and 0.009 Vs HCs, Fig 1 B). PPI increased serum CgA-FR, with a greater effect in TA, and quenched of the distinctive SLE-associated processing (Fig 1 C). CgA peptides did not correlate with disease activity in TA nor in SLE. However, in the homogeneous group of TA pts on PPI, arterial progression was associated with reduced a reduced antiangiogenic CgA potential (p=0.010). Conclusions: A selective processing of CgA is evident in SLE, whose molecular bases are unknown. TA associates with a greater increase in CgA-FR levels than SLE during PPI therapy. CgA peptides do not correlate with disease activity. Antiangiogenic CgA potential is reduced in TA pts on PPI undergoing progression, underlining the importance of angiogenesis in arterial remodelling and suggesting an involvement of CgA peptides in TA pathogenesis. Disclosure of Interest: None declared